2018
DOI: 10.1016/j.ejogrb.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the risk factors and symptoms associated with endometrial cancer in British South Asian and British White women

Abstract: Greater effort is needed to raise awareness in both the BW/BSA communities of the symptoms associated with EC that should prompt medical review. Educational efforts are required to overcome the reported perception that EC is synonymous with cervical cancer and cannot be detected by cervical screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Further work is needed to determine whether this reflects a genuine change in age-standardised incidence rates within South Asian populations, or whether the rise is a result of an increasing, aging, or a demographically changing South Asian population within Leicestershire. In a previous study, we have shown that although EC patients of South Asian ethnicity had greater awareness of unscheduled vaginal bleeding being associated with a malignancy, they were less aware of the most common EC risk factors or the suspected cancer referral pathway, as compared to patients of White ethnicity [ 30 ]. Numerous barriers to help-seeking behaviour have been reported, in particular language [ 31 ], which could potentially delay an EC diagnosis; therefore, raising the awareness of EC and its most common presenting symptoms could facilitate investigations and encourage detection at the earliest point of contact.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to determine whether this reflects a genuine change in age-standardised incidence rates within South Asian populations, or whether the rise is a result of an increasing, aging, or a demographically changing South Asian population within Leicestershire. In a previous study, we have shown that although EC patients of South Asian ethnicity had greater awareness of unscheduled vaginal bleeding being associated with a malignancy, they were less aware of the most common EC risk factors or the suspected cancer referral pathway, as compared to patients of White ethnicity [ 30 ]. Numerous barriers to help-seeking behaviour have been reported, in particular language [ 31 ], which could potentially delay an EC diagnosis; therefore, raising the awareness of EC and its most common presenting symptoms could facilitate investigations and encourage detection at the earliest point of contact.…”
Section: Discussionmentioning
confidence: 99%